An Annotated Translation Of “Techniques And Principles In Language Teaching” (Teaching Techniques In English As A Second Language - Sholihin (STKIP Taman Siswa Bima, 2017)
This study is an annotated translation. The object of the study is a book which is entitled techniques and principles in language teaching by Diana Larsen – freeman. The problems of this study are: (1) “what are the difficulties encountered by the researcher when translating techniques and principles in language teaching into Indonesian, and (2) ‘how are those difficulties solved in the translation?”. The purposes of this study are: (1) to attain factual information concerning the problems faced the researcher in translating the source text; and (2) to give plausible solutions to the difficulties. In conducting this annotated translation, the researcher answers the questions that emerge in the introspective and retrospective study. The result of the study covered two main points. First, finding revealed that from the twenty five most difficult problems, eight were in the form of grammatical structures, and seventeen.